Investigating the types and reasons of codeswitching in a formal setting: a case study of UiTM Kampus Bandaraya Melaka / Julfahanim Jumain - Jumain, Julfahanim (2011)
This case study was qualitatively done to investigate the types of codeswitching and the reasons of code-switching occur in a formal situation; classroom setting among a group of TESL students in UiTM Bandaraya Melaka. The four subjects were purposively sampling which their proficiency level were determined by using the Malaysian University English Test (MUET) selected from 55 TESL students to be investigated. The findings showed that there are two types of code-switching found during the presentations which are; inter-sentential and intra-sentential codeswitching. There are also several reasons found why they code-switched during the presentation which are to menisfest power, to obvibiate difficulty, to add emphasis, to lower language barrier and to reiterate messages. The instruments used in this case study were, observation of classroom presentation while the methodology used are, observation, audio recording and interview.